Modelling and validation of hybrid series active filter for power quality enhancement using OPAL-RT simulator - Shrivastava, Nitisha; Baliyan, Arjun (International Journal of Electrical and Computer Engineering (IJECE), 2025)
It is a known fact that the quality of power is degrading at a very fast rate. The reason behind this is harmonics in the power supply. The main motive is to reduce the harmonic pollution in the system for various combinations of the load. The method proposed in this paper consists of hybrid series active power filter (HSAPF) which is a combination of an active power filter connected in series and the passive filter in parallel with the load. In order to generate the compensating signals, synchronous reference method has been used and the tuning of the proportional integral (PI) controller is performed with grey wolf optimization technique. It provides the optimized values of controller parameters that are very much necessary to improve not only the transient but also the steady state characteristics of the system. For comparison purposes the tuning of PI controller is also done using the well- known particle swarm optimization technique. A comparative simulation analysis is done in MATLAB as well as the results are verified by using OPAL-RT 4510 real time simulator which proves that the suggested topology gives better results in terms of total harmonic distortion (THD) reduction.